Efeitos de fertilizantes nitrogenados no patossistema Puccinia triticina-Triticum aestivum - Minuzzi, Simone Gripa (2015)
Abstract – The objective of this study was to determine the biochemical changes caused by applying foliar fertilizers isolated or associated with the fungicide and the relationship of these changes with Puccinia triticina control in wheat. Two experiments were conducted, one in greenhouse and other in field conditions in 2014 year. In the greenhouse the plants were treatments with foliar fertilizers associated or not with fungicide in one application. In the field, the plants received treatments with fertilizers associated with fungicide. It was determined the activity of Guaiacol-peroxidase, hydrogen peroxide quantity (H2O2), lipid peroxidation, severity of Puccinia triticina and productivity parameters. In the greenhouse, all treatments with application of foliar fertilizers reduced the amount of H2O2 by induction of guaiacol peroxidase activity. The isolated fungicide provided greater stress to the plant, with higher accumulation of H2O2. In the field and greenhouse conditions, these same treatments with fertilizer when combined with fungicide had higher leaf rust control and productivity than treatment only fungicide, highlighting the treatment with foliar fertilizer Double Act®, with nitrogen and carbon, VittaSpray®, with foliar fertilizer several mineral elements, and also, the treatment with Dithane NT®.